Development of Character Education Evaluation Model (In Schools and Islamic Boarding Schools) - Muhammad Ridwan Fauzi; Aan Hasanah; Bambang Samsul Arifin (STKIP Yapis Dompu, 2023)
The research objective focuses on developing an evaluation model for character education in schools, madrasas and Islamic boarding schools with proper character education evaluation, so that these character values are actually internalized in the souls of students, displayed in good behavior, and finally emerge as a habit. cultured. This research uses a qualitative approach with content analysis techniques. Content Analysis Studies defines this method as a detailed and systematic examination of the content of a given set of materials for the purpose of identifying patterns, themes or biases. Research shows that the results of character education are more emphasized in the affective and psychomotor domains than the cognitive domains. Evaluation techniques that can be used include 1) Actualization of Character Education Values through Evaluation 2) Authentic Assessment as the Main Means of Implementing Character Education in Schools 3) Research Rubric 4) Evaluation of the Implementation of the Character Education Program by TIM. Evaluation of the results of character education is not only carried out by the teacher, but by a team consisting of teachers, principals, other school staff (administrative staff, laboratory assistants, technicians), school committees, parents, the general public, and also the students themselves to assess changes in attitude. to himself or his group.